2003
DOI: 10.1159/000071713
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthyroidism in Patients Older than 55 Years: An Analysis of the Etiology and Management

Abstract: Background: Hyperthyroidism is a common disease in the elderly. Although some studies on the prevalence of this thyroid disorder have been performed in the aged population, several aspects of hyperthyroidism, such as etiology and treatment effectiveness, have not been fully characterized in large series of aged patients. Objective: The aims of the present study were to determine the frequency of the diverse etiologies of hyperthyroidism, and to assess the effectiveness of therapy in adult patients older than 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 27 publications
2
46
0
3
Order By: Relevance
“…This theory is in accordance with our findings that T 3 levels in postmenopausal women are positively associated with breast cancer mortality. An important issue for future studies will be to evaluate the widespread, long-term use of T 4 treatment in TSH-suppressive doses for benign thyroid disease (30,31), and the management of women with subclinical hyperthyroidism (32,33,34). Such studies will contribute with important evidence whether or not to treat mild and/or subclinical thyroid disorders.…”
Section: T 3 (Quartile)mentioning
confidence: 99%
“…This theory is in accordance with our findings that T 3 levels in postmenopausal women are positively associated with breast cancer mortality. An important issue for future studies will be to evaluate the widespread, long-term use of T 4 treatment in TSH-suppressive doses for benign thyroid disease (30,31), and the management of women with subclinical hyperthyroidism (32,33,34). Such studies will contribute with important evidence whether or not to treat mild and/or subclinical thyroid disorders.…”
Section: T 3 (Quartile)mentioning
confidence: 99%
“…1,19,20,41 All types of hyperthyroidism occur in the elderly. Toxic multinodular goiter is the most frequent cause of spontaneous hyperthyroidism in the elderly in areas with a low iodine intake, whereas Graves' disease is more common in areas with a relatively high iodine intake such as the United States.…”
Section: Hyperthyroidismmentioning
confidence: 99%
“…Toxic multinodular goiter is the most frequent cause of spontaneous hyperthyroidism in the elderly in areas with a low iodine intake, whereas Graves' disease is more common in areas with a relatively high iodine intake such as the United States. 1,41,42 In aged patients, hyperthyroidism may also be precipitated by excess iodine intake from drugs or radiographic contrast agents. 1 When compared to younger patients, elderly hyperthyroid patients display fewer signs and symptoms.…”
Section: Hyperthyroidismmentioning
confidence: 99%
“…Moreover, several studies have also reported that dysfunction of the thyroid gland is a common clinical disease associated with aging (17)(18)(19)(20). Investigations into the relationships between thyroid status and cognitive abilities in humans have shown that a deficit in thyroid hormones induces severe anatomic and functional alterations of the nervous system, and intellectual impairment (21 -24).…”
Section: Introductionmentioning
confidence: 99%